Experimental study of a carbon dioxide direct-expansion ground source heat pump (CO2-DX-GSHP). (5th February 2018) - Badache, Messaoud; Ouzzane, Mohamed; Eslami-Nejad, Parham; Aidoun, Zine
Highlights: Experimental results of a DX-GSHP are presented in heating mode. The increases in the inlet water temperature by 1 °C, decreases the COPH by 0.14. At low expansion valves opening, CO2 phase change occurs more rapidly. At low expansion valves opening, phase change requires less length for evaporation. Abstract: Recently, the use of natural refrigerants in air conditioners and heat pumps has raised special interest from industry and the scientific community. It is seen as one of the most promising alternatives to replace conventional refrigerants, especially in ground source heat pumps for many applications. This paper presents the results of an experimental study of a transcritical carbon dioxide direct-expansion ground coupled heat pump, in heating mode. A test facility of this system was instrumented and tested for different operating conditions. Overall system performance, evaporation phase change of CO2 inside the ground heat exchanger and effect of active borehole number on system performance were investigated. In the particular case of this work, the coefficient of performance of DX-GSHP using CO2 as refrigerant could reach 3.5.